(Meta)linguistic abilities of bilectal educators: the case of Cyprus. Issue 8 (13th September 2020) - Leivada, Evelina; Kambanaros, Maria; Taxitari, Loukia; Grohmann, Kleanthes K.
ABSTRACT: The present study examines whether bilectal Greek Cypriot educators are able to identify dialectal (Cypriot Greek) elements superimposed on the standard language (Standard Modern Greek) in a written variety-judgment task. By doing so, (meta)linguistic skills of bilectal teachers from Cyprus were put to the test and later compared to the results of monolingual native Standard Modern Greek-speaking teachers from Greece on the same task. The findings revealed important differences between the performance and the linguistic profiles of the two groups across all levels of linguistic analysis, pointing out to a sharp discrepancy between what counts as 'standard' in Cyprus and what the performance in the standard variety really corresponds to. The implications of these findings for classroom language instruction in bilectal contexts are discussed.